Preparation and Characterization of Chitosan Nanoparticles for Chemotherapy of Melanoma Through Enhancing Tumor Penetration - Guo, Hui; Li, Faping; Qiu, Heping; Liu, Jianhua; Qin, Sihao; Hou, Yuchuan; Wang, Chunxi (Frontiers in Pharmacology, 2020)
The poor solubility and permeability of most chemotherapeutic drugs lead to unsatisfactory bioavailability combined with insufficient drug concentration. In this study, positively charged nanoparticles based on chitosan were developed and synthesized to enhance tumor penetration capability of 10-Hydroxycamptothecin (HCPT) in order to improve the chemotherapeutic effect of melanoma. The HCPT encapsulated nanoparticles were noted as NPs/HCPT. NPs/HCPT was characterized by dynamic light scattering and zeta potential measurements. In addition, cell uptake, in vitro cytotoxicity and apoptosis of NPs/HCPT were further investigated. The average diameter of NPs/HCPT was approximately 114.6 ± 4.1 nm. The viability of murine melanoma B16F10 cells was significantly decreased due to interaction with NPs/HCPT. These investigations implied that cationic NPs/HCPT could be potentially applied as a promising drug delivery nanosystem.